Organisation of Self-Government in the Republic of Macedonia - Fazliu, Ramiz (European Journal of Multidisciplinary Studies, 2016)
The subject of this paper is the constitutional and legal regulation of local self-government system in the Republic of Macedonia, territorial division, the process of reforming and building this system since the independence of the Republic of Macedonia from the former federation of Yugoslavia. With the intention of functioning and materialization according to democratic principles, since the independence of Macedonia the system of local self-government has undergone through continuous reform process. These reforms first of all are mostly related to the territorial division of local self-government units, seeking the most appropriate model which would be appropriate to the general developments of Macedonia. In this paper is analyzed the role and the constitutional and legal position of local self-government units, in this case the municipality, as the only unit of local self-government, its legal status, competences, representative and executive bodies, financing and the process of decentralization. It is also analyzed the model of organization of local self-government in the city of Skopje, as a capital of the Republic, in the form of community of municipalities in the city and the impact of the Ohrid Agreement on the regulation and functioning of local self-government in Macedonia.
Keywords: Local Self-government, Macedonia, Municipality, agreements